ANALISA SISTEM PERSEDIAN DENGAN METODE STRUKTURAL EQUATION MODELLING (STUDI KASUS: PD GENTONG MAS) - Rifa Nurafifah Syabaniah (Jurnal Techno Nusa Mandiri, 2016)
This study discusses how the process of analyzing the warehouse inventory system in PD Gentong Mas palm sugar town of Garut and test how effective research model variables Iklila Muzayyanah by testing using Amos Application version 22. Results Analysis of the warehouse inventory system in PD Gentong Mas palm sugar is effective for production with a medium size (S), this is evidenced by the results of testing the validity indicator S<--- Production 0.385 and 0.76 are in the reliability test. While testing how effective Variables Research Model IklilaMuzayyanah, if it is used to test the warehouse inventory system in PD GentongGarut Mas palm sugar, is not fit. Based on the test results are known fitness model Probability values less than the recommended value, which is less than 0.05. K